IMPLEMENTASI MOBILE MARKETING DALAM MENINGKATKAN JUMLAH PENJUALAN DAN CITRA PELAKU USAHA PRODUK BERBASIS KEARIFAN LOKAL - Amiludin; Nurjaman, Agus Dade (Jurnal Al Maesarah, 2025)
Jayamekar Village is renowned for its stone mortar craftsmanship, yet most entrepreneurs still rely on traditional marketing, limiting market reach. Despite the products' cultural value, promotion remains localized, limiting sales growth. This study implements mobile marketing to enhance digital strategies for increased sales and improved product image. Using the Participatory Action Research (PAR) method, entrepreneurs actively participate in training on digital platforms such as WhatsApp Business, Facebook Ads, and Shopee over four weeks. Results showed notable improvements: regular customers increased from 10 to 14–20, monthly transactions rose from 25 to 35, social media engagement surged from 30 to 250 interactions, and online sales grew from 5 to 30 units. Entrepreneurs who adapted quickly became role models, fostering collaboration. The study highlights mobile marketing's role in accelerating digital transformation for local products, contributing to economic growth. Unlike previous research on MSMEs, this study emphasizes direct engagement through PAR, ensuring practical application and sustainability. Future studies should explore long-term evaluations and alternative digital platforms for broader market reach.